Salmonella as a model for non-cognate Th1 cell stimulation - O'Donnell, Hope; Mcsorley, Stephen (Frontiers in Immunology, 2014)
Salmonella has been a model pathogen for examining CD4 T cell activation and effector functions for many years due to the strength of the Th1 cell response observed during Salmonella infections, the relative ease of use of Salmonella, the availability of Salmonella-specific T cell reagents, and the well-characterized nature of the model systems, the pathogen, and the immune response elicited. Herein, we discuss the use of Salmonella as a model pathogen to explore the complex interaction of T cells with their inflammatory environment. In particular, we address the issue of bystander activation of naïve T cells and non-cognate stimulation of activated and memory T cells. Further, we compare and contrast our current knowledge of these non-cognate responses in CD8 versus CD4 T cells. Finally, we make a case for Salmonella as a particularly appropriate model pathogen in the study of non-cognate CD4 T cell responses based on the strength of the Th1 response during infection, the requirement for CD4 T cells in bacterial clearance, and the well-characterized inflammatory response to conserved molecular patterns induced by Salmonella infection.